Macroeconomics for business : the manager's way of understanding the global economy - Davidson, Lawrence S., (Cambridge University Press, 2020)
Interpreting and applying macroeconomic analysis to the global economic environment and understanding the tools used to do so is fundamental to making good managerial decisions. Presuming no background in economic theory and prioritizing international application, this textbook introduces macroeconomics to business students. It explains how to understand domestic and global macroeconomic developments, policies, and data, and makes extensive use of case studies and data sets to present modern macroeconomics in a globalized world. Each chapter has several specific data exercises and practices as well as an international application focusing on the global perspective. By providing a host of international material, this book is useful for instructors and students around the globe.